Populações tradicionais, ação comunitária, capital social e educação: um debate necessário à efetivação de reservas extrativistas na Amazônia - SILVA, José Bittencourt da (Universidade Federal do Pará, 2020)
Theoretically, a traditional population has, at least in part, a history of low environmental impact, and has in the present interest in maintaining or obtain the control over the territory that inhabit. The aim of this paper is to make reflections about these populations, objecting to expose and talk about their most important problems, such as the difficulty to work in community and the problem of low social capital in the context of extractive reserves (RESEX) in the Amazon. In this context, the paradigm of education of the field is an alternative to authoritarian model education in the RESEXs, especially in the RESEX Ipau-Anilzinho, Pará state. Methodologically, this paper result of a literature search made in the libraries physical and virtual, and personal collection. What follows are discussions about the subject indicated, from the literature examined.